Port Facility Improvement and Vessel Call Dynamics: A Qualitative Analysis of Institutional and Infrastructure Constraints in a Regional Feeder Port - Suryadi, Awel; Togatorop, Agus Leonard (Universitas Hang Tuah, 2026)
Regional feeder ports play a critical role in supporting logistics connectivity and regional economic growth; however, their performance is often constrained by limited facilities and governance issues. This study aims to examine the relationship between port facility conditions, vessel call dynamics, and institutional constraints affecting the development of a regional feeder port. A qualitative interpretative approach was employed, using field observations, in-depth interviews with port authorities and stakeholders, and document analysis. Data were analyzed through thematic reduction, categorization, and analytical interpretation. The findings reveal that low vessel calls are not primarily driven by insufficient demand but by inadequate core facilities such as channel depth, berth length, and cargo handling equipment. Furthermore, overlapping authorities and the absence of updated port master planning documents significantly hinder investment decision-making. This study highlights that port facility improvement must be preceded by institutional resolution to ensure effective and sustainable port development.